Cardiac rehabilitation - Vatansever Ağca, Fahriye (The European Research Journal, 2019)
Cardiovascular diseases are one of the majorcause of mortality globally. Coronary heart disease is the largest subset of cardiovascular disease. Although mortality rates decline during time, hospital discharge data as a measure of morbidity rates are stable, leading to larger pool of patients eligible to benefit from cardiac rehabilitation. Cardiac rehabilitation is a multi-disciplinary approach including exersize training, patient counselling, education and nutritional guidance. Despite the many known benefits of cardiac rehabilitation, refferal and participation rates remainlow and interventions to increase its use need to be developed.